Case GRAB - Afiqah Dania Ezzatul; Daisy Mui Hung Kee; Hämäläinen Tuovi; Nurul Aqilah Dewi Binti Roslan; Saussez Charlotte (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
Grab is the leader of taxi transportation today in Southeast Asia, but how can it stay leader in the years to come? This paper is a research work about Grab company from past, present and future. From Grab creation in 2012 till today the company’s shape has changed a lot. Since the moment Grab bought Uber’s Southeast Asia operations, the ride-hailing app has always been first transport company in Malaysia and many other southern Asian countries. Grab success is mainly due to the fact that the company is always able to jump on to new market opportunities and always seeking for improvement. After telling more about Grab’s history and way of functioning, we focus on two main propositions of improvement: Rent-ACar, and Green Grab. This research works also as a guideline for Grab’s CEO on what to do in the future for his business to stay competitive.